Pertanggungjawaban Hukum Lingkungan atas Banjir Rob Semarang dalam Perspektif SDGs 13 Climate Action - Farras Eknu Albin; Risqi Budi Santoso; Christian Bagas Dewantara; Rois Faisal Amin; Muhammad Adymas Hikal Fikri (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
ABSTRACT Tidal flooding (rob) in Semarang has evolved into a persistent and complex environmental problem, reflecting the interaction between climate change impacts and weaknesses in environmental governance. This phenomenon is not only caused by natural factors such as sea level rise, but is also significantly influenced by anthropogenic activities, including land subsidence due to excessive groundwater extraction, uncontrolled coastal development, and inadequate spatial planning. As a result, tidal flooding has generated serious social, economic, and ecological consequences for coastal communities. This study aims to analyze environmental legal liability for tidal flooding in Semarang within the framework of legal protection, while also examining its relevance to the Sustainable Development Goals (SDGs), particularly Goal 13 on Climate Action. This research employs a normative legal method using statutory, conceptual, and case approaches to evaluate environmental regulations, legal doctrines, and principles of liability. The findings indicate that environmental legal liability remains weak due to regulatory fragmentation, lack of institutional coordination, and ineffective law enforcement. Preventive instruments such as environmental permits and spatial planning regulations have not been optimally implemented, while repressive measures remain limited. Furthermore, the absence of a clear and integrated liability framework contributes to legal uncertainty and weak accountability among stakeholders. This study concludes that strengthening environmental legal liability through integrated regulations, adaptive governance, and consistent law enforcement is essential to support climate action and ensure effective legal protection against tidal flooding in Semarang City. Keywords: environmental law, legal liability, tidal flooding, climate action, SDGs 13, Semarang